Studi Komparasi Pemaknaan Agama dalam Partai Politik PPP, PKB, PAN dan PKB Kota Tasikmalaya - Edi Kusmayadi (Jurnal Ilmu Politik dan Pemerintahan, 2020)
From four political party used as object of this research, there was political party separated between religion and politic, but religion values internalized to the politic behavior then concreted to the practical politic. There was also politic party where religion and politic wasn’t separated, religion position untegrated to politic and formally religion being principal party. While in other perception, religion specialized from politic, between religion ang politic was separated but there still connecity. Religion unincluded to political party, religion has functioned as basic of moral and ethical politic. So can concluded that Islamic religion positioned and meaned typicly on politic party. The population in this research is executor of politic party. Considering many of the executor are being a target, so the sampling used is simple random sampling technique. The method used to collected data is documentation, the data that collected analized by content analyze. The analyze sharped by seeing the aspect which is backgrounded a platform, include development political party situation. Simbolic analyze, simbolic definition, attribute ang politic party slogan analyzed by cultural knowledge, religion and tradition meaning or people costum ang political world.